E-commerce: Development Opportunities and Threats - Ramazanov, А.; Karimova, М. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2023)
The article characterizes significance and role of the basic conditions that form the electronic commerce ("e-commerce"). The development of information technologies and communications, primarily the Internet, form a new business environment. There is a formation of electronic commerce ("e-commerce"), which is a mirror image of real commerce. E-commerce is a market that is emerging in the Internet space. In the Internet space, by analogy with the traditional market, there are sellers, buyers, intermediaries, selling and buying products and services. The activity of formation and intensity of use of e-commerce has become not just an important feature, but a paradigm for the functioning of modern business. Business is transferred to the Internet space. The motivation for the transition of business to the form of e-commerce in the Internet space is the lower costs of doing business, saving money. At the moment, the sphere of circulation allows to implement business processes, making maximum use of Internet technologies, since the stage of distribution and exchange of profits of social reproduction is provided here. Differences in opinions about the essence and content of e-commerce are revealed. The essence and content of e-commerce determine the ongoing transactions in the network economy. The development of e-commerce in the world economy is characterized. It is concluded that the dynamic development of e-commerce is shown by the trading platforms of China. To determine the potential for the development of e-commerce in Kazakhstan, the UNCTAD B2C e-commerce index was used. The competitive advantages of Kazakhstan in the development of e-commerce include the literacy of the population, the use of the Internet. It is revealed that e-commerce contains development opportunities and threats.